(untitled) (Texas Journal of Medical Science, 2025)
PLA2G2E plays a pro-survival and pro-reparative role in periinfarction neurons, contributing to recovery after stroke. PLA2G2E levels below 0.580 units are associated with an increased risk of mortality. Exceeding this threshold significantly improves survival and functional outcome (according to the Rankin and Bartel scales). Measuring PLA2G2E levels on the first day after a stroke can help assess the prognosis and adjust treatment to improve survival and restore function.